Molecular identification of Paramphistomum epiclitum (Trematoda: Paramphistomidae) infecting buffaloes in an endemic area of Pakistan - Komal, Maria; Afshan, Kiran; Firasat, Sabika; Fuentes, Màrius V. (The Thai Journal of Veterinary Medicine, 2021)
This study determined the molecular characterization of Paramphistomum epiclitum using the second internal transcribed spacer (ITS-2) grouping and secondary structure analysis from buffaloes in Khyber Pakhtunkhwa province, Pakistan. Paramphistomes were collected from the rumen of 25 infected buffaloes and their DNA was separated. DNA was intensified, followed by sequencing. Phylogenetic examinations were carried out using the Maximum Composite Likelihood approach. The results revealed extensive intraspecific and interspecific varieties among different paramphistomid species. The sequences in the present study (GenBank accession number: MW481321 and MW481322) were compared to 46 reference sequences of Paramphistomum and other trematode data from GenBank. The results revealed the existence of two genotypes of P. epiclitum with six intraspecific single nucleotide polymorphisms, most closely associated with Indian isolates with an evolutionary divergence in the range of 0.00-0.015. The phylogenetic tree analysis of Paramphistomum spp. with other representative isolates in different locations clearly showed the existence of two P. epiclitum genotypes in Pakistan. The derived secondary structures for both genotypes presented structural similarities with the core four-helix domain structure. Likewise, the results showed the phylogenetic utility of the ITS-2 sequence – secondary structure information for inductions at higher ordered levels and the need for accurate species identification. The results of this study also have implications for the diagnosis and control of rumen flukes in the region.